High Frequency of Early Repolarization and Brugada‐Type Electrocardiograms in Hypercalcemia. Issue 1 (11th August 2015) - Sonoda, Keiko; Watanabe, Hiroshi; Hisamatsu, Takashi; Ashihara, Takashi; Ohno, Seiko; Hayashi, Hideki; Horie, Minoru; Minamino, Tohru
Abstract : Background: J wave, or early repolarization has recently been associated with an increased risk of lethal arrhythmia and sudden death, both in idiopathic ventricular fibrillation and in the general population. Hypercalcemia is one of the causes of J point and ST segment elevation, but the relationship has not been well studied. The aim of this study was to examine the effects of hypercalcemia on J point elevation. Methods: Electrocardiographic findings were compared in 89 patients with hypercalcemia and 267 age‐ and sex‐matched healthy controls with normocalcemia. The association of J point elevation with arrhythmia events in patients with hypercalcemia was also studied. Results: The PR interval and the QRS duration were longer in patients with hypercalcemia than in normocalcemic controls. Both the QT and the corrected QT intervals were shorter in patients with hypercalcemia compared with normocalcemic controls. Conduction disorders, ST‐T abnormalities, and J point elevation were more common in patients with hypercalcemia than normocalcemic controls. Following the resolution of hypercalcemia, the frequency of J point elevation decreased to a level similar to that noted in controls. During hospitalization, no arrhythmia event occurred in patients with hypercalcemia. Conclusion: Hypercalcemia was associated with J point elevation.